Metal-free bifunctional carbon electrocatalysts derived from zeolitic imidazolate frameworks for efficient water splitting - Lei, Yaojie (2020)
Metal-free carbon catalysts have attracted great interest because of their high electrical conductivity, tailorable porosity and surface area, affordability, and sustainability. In particular, their bifunctional activity for hydrogen and oxygen evolution reactions (HER and OER) is attractive for electrochemical splitting of water. However, pristine carbon materials have low activities for HER/OER. Here, a high-performance carbon electrocatalyst is demonstrated by first pyrolyzing a metal-organic framework (MOF), i.e., zeolitic imidazolate framework-8 (ZIF-8), followed by optimized cathodic polarization treatment (CPT). Pyrolyzing ZIF-8 produces a highly N-doped (8.4 at%) carbon material having a large specific surface area of 1017 m2 g1 with micro and mesopores. CPT in 0.5 M H2SO4 for up to 8 hours modulates the composition of N- and O-containing surface functional groups of the pyrolyzed ZIF-8 without sacrificing its large surface area and pore size distribution. After the 6-hour CPT, this material shows an excellent HER activity in 0.5 M H2SO4 electrolyte with an overpotential of 155 mV, a Tafel slope of 54.7 mV dec1, and an exchange current density of 0.063 mA cm2. And the 4-hour CPT results in excellent OER activity in 0.1 M KOH electrolyte with an overpotential of 476 mV and a Tafel slope of 78.5 mV dec1. In a demonstration, these two carbon electrocatalysts steadily run a two-electrode water electrolyzer at a current density of 10 mA cm2 over 8 hours under a potential of 1.82 V with a Faradaic efficiency of 98.0-99.1% in 0.1 M KOH electrolyte. The superior activity of the designed carbon electrocatalysts can be attributed to the functional group composition modulation achieved by CPT. High-performance metal-free carbon electrocatalysts derived from MOFs show excellent potentials for energy and environmental applications.